Impact of High Temperature on the Compressive Strength of ECC. (25th June 2014) - Shang, Xingyan; Lu, Zhoudao
Abstract : The influence of different cooling regimes (quenching in water and cooling in air) on the residual mechanical properties of ECC (engineered cementitious composites) exposed to high temperature up to 800°C was discussed in this paper. The specimens quenching in water gained better mechanical properties than the ones cooling in air. The strengthening effect of quenching for specimens subjected to 800°C was more significant than for the ones subjected to 400°C. The microstructural characterization is examined before and after exposure to fire deterioration by using scanning electron microscopy. Results from the microtest well explained the mechanical properties variation of postfire specimens.